Two microphone acoustic feedback cancellation in digital hearing aids: A step size controlled frequency domain approach - Pradhan, S.; George, N.; Albu, F.; Nordholm, Sven (Elsevier, 2018)
© 2017 Elsevier Ltd The feedback cancellation performance of behind the ear hearing aids can be improved by employing two microphones in the feedback cancellation process. A frequency domain implementation of feedback cancellation in a two microphone behind the ear hearing aid has been proposed in this paper. A frequency domain step size control scheme has been further introduced to improve the convergence behaviour. The implementation of a the frequency domain step size control method requires the microphone input signal as well as the loudspeaker output signal to be uncorrelated. In order to reduce the correlation effects and enable such an implementation, we have incorporated frequency shifting in the forward path. The proposed approach has been shown to provide improved convergence behaviour as well as offer enhanced speech quality. Further, the proposed scheme is expected to offer a reduced computational load for longer feedback paths.